Investigation of partial discharges in non-woody kenaf based pressboard under influence of moisture - Rizda Fitri Kurnia; Norhafezaidi Mat Saman; Mohd Hafizi Ahmad; Zainuddin Nawawi; Nur Azalia Azrin; Mohd Aizam Talib (Institute of Advanced Engineering and Science, 2022)
The most crucial parts that decide the transformer’s lifetime are the solid insulation of the power transformer, especially the pressboard and kraft paper. The life of the insulation is significantly influenced by the presence of water in the insulation. This paper presents a study on partial discharge (PD) on the existing normal pressboard (NP) and the newly developed Kenaf-polypropylene pressboard (KPP). Also, the moisture content of the pressboard varied between 0%, 1%, and 3% by the percentage weight of different methods. After the initiation of PD, the surface deterioration analysis was performed by using scanning electron microscopy (SEM). The results from the study revealed that KPP shows superior performance in mitigating PD. At 0%, 1% and 3% moisture contents, KPP showed 89%, 83% and 25% reductions in average PD magnitude, respectively. Overall, the kenaf composite pressboard has better PD resistance, which is one of the things to think about when insulating a transformer.